Obraz generala Hludova v slovenskom perevode p'esy M. A. Bulgakova "Beg" - Kaloh Vid, Natalia (Slavia Centralis, 2024)
The article focuses on the analysis of allusions and attributed and unattributed references to the Revelation and other biblical texts referring to the main protagonist in Bulgakov’s drama Flight, the White Guard general Roman Hludov, in the Slovenian translation by Borut Kraševec (2016) from the point of consistency and preservation. The historical apocalypse in the drama is representative of the destruction of the old world, loss of homeland, loss of identity, deconstruction of old ideals and degradation of the human. Intertextual figures that Bulgakov intentionally uses to establish parallels with the biblical prophecy about the end of the world represent an important feature of the drama’s stylistic diversity. If the translator omits them, he deprives the text of one of the key features of the author’s significantly ambivalent style. The present paper investigates how, and if, these features are preserved in the Slovenian translation, and which translation strategies Kraševec used.
Keywords: allusions; aluzije; Bulgakov, Mihail Afanasjevič; citation; intertekst; intertext; navedek; prevodi; translation